1991
DOI: 10.1128/jvi.65.10.5391-5400.1991
|View full text |Cite
|
Sign up to set email alerts
|

PEA1 and PEA3 enhancer elements are primary components of the polyomavirus late transcription initiator element

Abstract: The circular polyomavirus genome is transcribed from divergent promoter regions. Early mRNAs are initiated from a transcription complex formed at a TATA motif, the site of binding of transcription factor TFIID. Early transcription is promoted at a distance by the viral enhancer, which includes DNA motifs bound by cellular proteins of the PEAl and PEA3 families of transcription activators. In contrast, the predominant viral late mRNAs are initiated within the viral enhancer, which lacks a TATA motif, near the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…The stretch of DNA between the Inr sequence and the A ⁄ T-rich region in the DPP-III promoter contains a GC box (Sp1-binding motif) and two Ets-1 ⁄ Elk-1-binding motifs. Both of these transcription factors are known to help in recruitment of the transcription initiation assembly [27][28][29] and therefore this arrangement of nucleotides in the DPP-III promoter is probably responsible for the strong promoter activity of DPP-III in U87MG cells. Deletion analysis of the DPP-III promoter revealed that the region between )781 and )485 bp contains several transcription factor binding motifs such as USF, C ⁄ EBP and Sp1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The stretch of DNA between the Inr sequence and the A ⁄ T-rich region in the DPP-III promoter contains a GC box (Sp1-binding motif) and two Ets-1 ⁄ Elk-1-binding motifs. Both of these transcription factors are known to help in recruitment of the transcription initiation assembly [27][28][29] and therefore this arrangement of nucleotides in the DPP-III promoter is probably responsible for the strong promoter activity of DPP-III in U87MG cells. Deletion analysis of the DPP-III promoter revealed that the region between )781 and )485 bp contains several transcription factor binding motifs such as USF, C ⁄ EBP and Sp1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5, 3' deletion from the position +65 to +31 slightly increased the CAT expression, suggesting the presence of a weak repressing sequence in this deleted region. Each of the internal deletions of the putative E2F-binding sequence [28], the tran- scription-initiation site and the putative PEA3-binding sequence [29] decreased the CAT expression, suggesting the important roles of these sequences in promoter function. As shown in Fig.…”
Section: Mapping Of the Target Region In The Pcna Gene Promoter For Rmentioning
confidence: 99%
“…NIH 3T3 cells were transfected with DNA by calcium phosphate coprecipitation and glycerol shock as previously described (83) or with Lipofectamine (20 l of Lipofectamine/60-mm-diameter plate) per directions by Gibco-BRL. MOP-3T3 and MOP-3T6 cells were transfected with DNA with Lipofectamine, and COS1 cells were transfected with Lipofectace (Gibco-BRL).…”
mentioning
confidence: 99%